Pharmacological management of obesity an endocrine society clinical practice guideline - Apovian, Caroline M.; Aronne, Louis J.; Bessesen, Daniel H.; McDonnell, Marie E.; Murad, M. Hassan; Pagotto, Uberto; Ryan, Donna H.; Still, Christopher D. (REPRODUCTIVE ENDOCRINOLOGY, 2015)
Objective: To formulate clinical practice guidelines for the pharmacological management of obesity. Participants: An Endocrine Society-appointed Task Force of experts. This guideline was co-sponsored by the European Society of Endocrinology and The Obesity Society. Evidence: This evidence-based guideline was developed using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE ) system to describe the strength of recommendations and the quality of evidence. Conclusions: Weight loss is a pathway to health improvement for patients with obesity-associated risk factors and comorbidities. Medications approved for chronic weight management can be useful adjuncts to lifestyle change for patients who have been unsuccessful with diet and exercise alone. Many medications commonly prescribed for diabetes, depression, and other chronic diseases have weight effects, either to promote weight gain or produce weight loss. Knowledgeable prescribing of medications, choosing whenever possible those with favorable weight profiles, can aid in the prevention and management of obesity and thus improve health.